Probing the release of the chronobiotic hormone melatonin from hybrid calcium alginate hydrogel beads - Vlachou Marilena; Siamidi Angeliki; Goula Efstratia; Georgas Panagiotis; Pippa Natassa; Karalis Vangelis; Sentoukas Theodore; Pispas Stergios (Acta Pharmaceutica)
A variety of commonly used hydrogels were utilized in the preparation of calcium alginate beads, which incorporate the chronobiotic hormone melatonin (MLT). The in vitro release of the hormone in aqueous media at pH 1.2 and 6.8 was probed in the conjunction with the swelling of the beads and their thermal degradation properties. It has been found that the release of MLT from the beads was reversibly proportional to the extent of their expansion, which depends on the molecular mass/viscosity of the biopolymers present in the beads; the higher the molecular mass/viscosity of the hydrogels the greater the beads swelling and the less the MLT’s release. Thermogravimetric analysis (TGA) data support the presence of the components in the hybrid hydrogel beads and elucidate their effects on the thermal stability of the systems. Thus, the physicochemical properties of the biopolymers used, along with their stereoelectronic features modulate the release of MLT from the beads, providing formulations able to treat sleep onset related problems or dysfunctions arising from poor sleep maintenance.